Depresyjne zaburzenia nastroju u kobiet po narodzinach dziecka - Kossakowska-Petrycka, Karolina; Walęcka-Matyja, Katarzyna (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
This article focuses on depressive mood disorders that affect women after delivery. The paper presents diagnostic criteria of three types of depressive mood disorders, characteristic to this circumstances and multifactorial etiology. This information take notice of necessity for further research because of impact postpartum disorders on mother-child relationship and correct child development.